Collaborative Load Balancing and Effective Channel Allocation for Cluster-Based MANETs (International Journal of Innovative Research in Computer Science & Technology, 2020)
Mobile ad hoc network is a wireless network  group of mobile devices having no infrastructure. Load  balancing is an important problem in such networks due to  dynamic topology of the nodes. Many protocols are  developed to improve the bandwidth, energy efficiency and  throughput of these networks. With the increasing use of  MANETs they are evolving wit use of applications and for  non- uniform load distribution it’s difficult to manage the  load. Load balancing provides a single internet service from  multiple servers as a commonly used application.  Multicasting support at the link layer is essential for the  efficient use of network resources. system propose a light  weight dynamic channel allocation scheme for MANET.  The system compares two algorithms DCA -TRACE and  CMH-T RACE to provide support for non-uniform load  distributions and propose CDCA-TRACE. It increases the  number of source nodes and reduce the number of  collisions, energy consumptions and average absolute  IPDV drastically.
Keywords: CSMA; Dynamic channel allocation; Load balancing; Mobile ad hoc networks